Failure of Conflict to Modulate Central Executive Network Activity Associated with Delusions in Schizophrenia - Speechley, William J.; Woodward, Todd S.; Ngan, Elton T. (Frontiers in Psychiatry, 2013)
Dual-stream modulation failure (DSMF) proposes that dysfunctional regulation of logical and intuitive decision-making processes by conflict and emotional salience may be the underlying cognitive mechanism for the formation and maintenance of delusions in schizophrenia. The present study utilizes a combination of emotionally salient and neutral stimuli in conflict and non-conflict conditions in a sentence verification task to test specific hypotheses predicted by the model. Twenty-one patients with schizophrenia and 21 controls completed a sentence verification task with fMRI acquisition. The results are consistent with the predictions based on the conflict modulation component of the model, but do not support the emotional modulation component of the model.